(untitled) (Vietnam Journal of Community Medicine, 2024)
Background: Endoscopic Retrograde Cholangio Pancreatography (ERCP) is preferred in the diagnosis and treatment of some pancreaticobiliary diseases, including biliary drainage in the emergency treatment of acute cholangitis. The purpose of this study is to study the treatment results and safety of ERCP in the treatment of acute cholangitis in elderly patients. Patients and method: A retrospective descriptive case series of patients aged 80 years undergoing ERCP for biliary drainage in the emergency management of acute cholangitis at Thong Nhat Hospital in Ho Chi Minh City from 12/2022 - 11/2023. Results: There were 24 patients with a mean age of 88,7 ± 7,8, with the eldest at 98 years old. More than 90% of patients ≥ 80 years old have ASA- II, III. All of the patients ≥ 80 moderate and severe acute cholangitis according to Tokyo guidelines 2018. The rate of successful biliary catheterization was 83,3%. The rate of successful emergency bile drainage is 100%, in which the rate of removal of common bile duct stones is 44,4%. Complication rate of ERCP in the study was 20%, of which acute pancreatitis was 10%, most of the complications were mild. Conclusions: ERCP is the safe, effective technique for the emergency management of acute cholangitis in elderly patients.